Reflection of information about obligations in accounting (financial) statements - N. V. Tkachuk (Путеводитель предпринимателя, 2021)
The interpretation and assessment of the organization’s liabilities is important for determining the amount of equity capital, which characterizes the well'being of the owners of the organization. The author highlighted the shortcomings of the current legislation in regulating the formation of information about the obligations of the organization. The article substantiates the incorrect use of the term «obligations» in relation to accounts payable. The analysis of the characteristics of liabilities noted in IFRS for their compliance with certain financial and business transactions. Accounts payable have been identified, which are not reflected in the accounting (financial) statements of the organization.